Metabolic Effects of Breaking Prolonged Sitting With Standing or Light Walking in Older South Asians and White Europeans: A Randomized Acute Study. (7th November 2018) - Yates, Thomas; Edwardson, Charlotte L; Celis-Morales, Carlos; Biddle, Stuart J H; Bodicoat, Danielle; Davies, Melanie J; Esliger, Dale; Henson, Joe; Kazi, Aadil; Khunti, Kamesh; Sattar, Naveed; Sinclair, Alan J; et al.
Abstract: Background: Prolonged sitting is common in older adults and is associated with insulin resistance and poor cardiometabolic health. We investigate whether breaking prolonged sitting with regular short bouts of standing or light walking improves postprandial metabolism in older white European and South Asian adults and whether effects are modified by ethnic group. Methods: Thirty South Asian (15 women) and 30 white European (14 women) older adults (aged 65–79 years) undertook three experimental conditions in random order. (a) Prolonged sitting : continuous sitting during an observation period if 7.5 hours consuming two standardized mixed meals. (b) Standing breaks : sitting interrupted with 5 minutes of standing every 30 minutes (accumulating 60 minutes of standing over the observation period). (c) Walking breaks : sitting interrupted with 5 minutes of self-paced light walking every 30 minutes (accumulating 60 minutes of walking). Blood samples (glucose, insulin, triglycerides) and blood pressure were sampled regularly throughout each condition. Results: Compared with prolonged sitting, walking breaks lowered postprandial insulin by 16.3 mU/L, (95% CI: 19.7, 22.0) with greater reductions ( p = .029) seen in South Asians (22.4 mU/L; 12.4, 32.4) than white Europeans (10.3 mU/L; 5.9, 14.7). Glucose (0.3 mmol/L; 0.1, 0.5) and blood pressure (4 mm Hg; 2, 6), but not triglycerides, were lower with walking breaks, with no ethnic differences. Standing breaks did not improve any outcome. Conclusions: Breaking prolonged sitting with short bouts of light walking, but not standing, resulted in clinically meaningful improvements in markers of metabolic health in older adults, with South Asians gaining a greater reduction in postprandial insulin. Trial Registration: NCT02453204